Creating a typology of tobacco farms according to determinants of diversification in Valle de Lerma (Salta-Argentina) = Tipología de explotaciones tabacaleras de acuerdo a determinantes de diversificación en el Valle de Lerma (Salta-Argentina) - Chavez Clemente, Maria Daniela; Berentsen, Paul; Oude Lansin, Alfons (Consejo Superior de Investigaciones Científicas (CSIC), 2025)
The objective of this article is to identify typical tobacco farms according to determinants of diversification that can be used to explore possibilities of diversification in the province of Salta (Northwest of Argentina). National Agriculture Census data of 278 farms in the main tobacco production area of Salta were used for the analysis. The variables selected concerning determinants of diversification were: land area, irrigation, general capital goods and specific capital goods, ownership of land, education, off-farm work, and labour availability. The analysis of the principal components applied to 16 selected variables allowed to reduce the dimensionality of the data to four components. Those components were used to apply K-means cluster approach to classify the farms. Four clusters were determined. Cluster 1 and Cluster 2 are the largest clusters. These concern highly specialized tobacco farms. They differ regarding determinants for diversification due to different levels of education of the farmer and different levels of off-farm work. Both clusters are interesting for further analysis regarding diversification alternatives to maintain or improve income and to reduce soil degradation. Cluster 3 concerns large tobacco farms being somewhat less specialized than the farms in Clusters 1 and 2. Intensive tobacco production makes this group interesting for exploring diversification alternatives to improve soil conditions. Farms in Cluster 4 already have a high level of diversification with substantial livestock production. The presence of perennial pastures suggests a better soil management than the other clusters. This cluster looks appealing to investigate what can be done regarding diversification.